Impact of the Global COVID-19 Pandemic on the Slovak Economy (Tourism and Education) - Petrikovičová, Lucia; Petrikovič, Jozef; Kurilenko, Viktoria; Taraj, Martin; Kholov, Saidmukhidin; Azizi, Mahmoud (Journal of Education Culture and Society, 2023)
Aim. The aim of the contribution is to evaluate the effect of the COVID-19 pandemic on the Slovak economy. We analyzed the pertinent data relating to Slovakia's economy, tourism, and education infrastructures, and also the measures introduced during the pandemic which affected them.Methods. The paper is mainly based on descriptive, analytical and statistical methods, and based on global statistics data, studies, and research conducted in this field.Results. In 2020, the Slovak economy decreased by 9.3%. The reason was not only domestic measures against the spread of the coronavirus, but also a slump in foreign demand. The growth of the Slovak economy had already slowed during 2019, even before the onset of the COVID-19 disease. Extensive travel restrictions, especially at the international level, fundamentally affected the total number of visitors, in particular during the period March to August 2021. Almost 1.6 million visitors stayed in hotels, boarding houses, and other accommodation facilities in Slovakia during this period of the pandemic, which represented a decrease of almost 54% when compared to the pre-pandemic year of 2019.    Conclusion. The significant deterioration of the economy was the result of a large number of significant restrictive measures taken to stop the spread of the COVID-19 disease. The factor of the COVID-19 pandemic influenced the future of tourism and education, bringing changes to their direction and economic benefits. This pandemic has significantly affected education in Slovakia and worldwide, and we are following its transformation.